القيادة األصيلة ودورها في تعزيز الثقة التنظيمية دراسة تحليلية آلراء عينة من التدريسيين في كلية اإلدارة واالقتصاد - جامعة صالح الدين/أربيل - شيرواني, عبدالرحمن زرار عبدالرحمن; بكر, عيسى سعيد أبا; أحمد, شادان صباح (Sulaimani Journal for Humanities, 2022)
The research seeks to know the availability of the dimensions of authentic leadership among the Administrative Leadersof the College of Administration and Economics - Salah al-Din University / Erbil, from the point of view of a sample of college members, as well as to identify the role of authentic leadership in organizational trust. to achieve the research objectives a questionare designed and published on The research sample consisted of (107) teachers, and to measure the nature of the relationship and influence between the two variables, the statistical methods for the social sciences (SPSS) were relied in the analysis and testing of research hypotheses, which states that there are characteristics of authentic leadership with the availability of organizational trust in addition to the existence of a relationship and influnce Between the dimensions of authentic leadership and the organizational trust collectively and individually, and one of the most prominent results of the research is the agreement of the majority of the sample members on the existence of dimensions of authentic leadership and organizational trust in varying proportions, with a signtifice relationship and influence between the dimensions of authentic leadership and organizational trust at the macro and micro levels.
Keywords: authentic leadership; organizational trust; College of Administration and Economics Salahaddin University Erbil